2020
DOI: 10.1109/access.2020.2993872
|View full text |Cite
|
Sign up to set email alerts
|

Design of Automatic Lung Nodule Detection System Based on Multi-Scene Deep Learning Framework

Abstract: Nowadays, the efficient identification of the lung nodule greatly leads to the chance of lung cancer risk assessment. Hence, the exact locations of lung nodules are a critical and complicated task. Researchers in this area have been working widely for almost two years. However, previous computer-aided detection (CAD) modules, such as transforming CT, segmenting the lung nodule and extracting the features are mostly complex and time-consuming, because more modules will require the creation of a complete image p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The Multi-Scene DL Framework (MSDLF) is necessary for an efficient LND technique, and Zhang et al (17) suggested it, as it utilizes the vesselness filter. A 4-channel CNN architecture was developed by integrating 2 sets of images for the purpose of enhance the radiologist's ability to detect 4-stage nodules.…”
Section: Related Workmentioning
confidence: 99%
“…The Multi-Scene DL Framework (MSDLF) is necessary for an efficient LND technique, and Zhang et al (17) suggested it, as it utilizes the vesselness filter. A 4-channel CNN architecture was developed by integrating 2 sets of images for the purpose of enhance the radiologist's ability to detect 4-stage nodules.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, the features were fed to an ANN for classification needs. Since identified lung nodules greatly help in risk assessment of Lung Cancer, Zhang and Kong [231] designed a Multi-Scene Deep Learning Framework (MSDLF) to detect Lung Nodule from Lung CT images.…”
Section: Anifah Et Almentioning
confidence: 99%
“…ReLU is applied here as activation function along with Softmax layer which is applied fully to connect the layer and finally it produces the result [13]. This paper [14] proposed an automatic detection of lung tumor using public dataset of LIDC-IRDI. It uses MultiScene Deep Learning Framework which provides CT lung images as input and obtains probability distribution of distinct gray levels using threshold segmentation.…”
Section: Related Workmentioning
confidence: 99%